(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Comprehensive measures aimed at the development of medicine are being implemented in our country, particularly to reduce functional and organic disorders of the liver, its diseases, and complications, as well as to improve methods of treatment and prevention of these conditions, achieving significant results. The liver plays a leading role in the structure of digestive system pathologies, diseases, and mortality causes. Disorders of the digestive system are based on developmental abnormalities, dietary violations, and the structural and functional state of the digestive process. Scars after abdominal surgery can be of three types. Normotrophic scars are almost identical to the skin and appear as a thin white line after complete healing. Hypertrophic scars rise above the skin surface and are bright red. Atrophic scars are located below the skin level and include stretch marks and traces.